Pengembangan Kepribadian Guru dalam Perspektif Islam untuk Membentuk Karakter Pendidik yang Inspiratif - Andi Ari Wibowo; Rina Putriana; Kamil Rabbani Muhammad Zaidan; Hazna Selvia Kamilah; Mursidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education serves as a fundamental pillar in shaping the quality of human resources, with teachers holding a strategic role as agents of change and character builders for students. However, the current educational reality reveals a crisis of character and exemplary leadership that urgently needs addressing through the strengthening of personal competencies. This research aims to analyze the development of teacher personality from an Islamic perspective and explain how the integration of these values can form inspirational educators. Employing a qualitative approach with a library research design, this study examines various classical and contemporary literatures related to personality and Islamic education. The results indicate that holistic teacher personality development, covering physical, intellectual, spiritual, and emotional (qalb) dimensions, is the primary key to forming teachers who are not only capable of transferring knowledge but also serving as role models (uswah hasanah). The integration of fundamental Islamic values such as sincerity, patience, and compassion is proven to create inspirational educators with strong spiritual and emotional depth, thereby enabling them to drive positive transformation in students.